Toward an Ecological Framework for Assessing Reservoirs of Vector-Borne Pathogens: Wildlife Reservoirs of Trypanosoma cruzi across the Southern United States - Hodo, Carolyn L (ILAR J, 2017)
Wildlife species are critical for both feeding vectors and serving as reservoirs of zoonotic vector-borne pathogens. Transmission pathways leading to disease in humans or other target taxa might be better understood and managed given a complete understanding of the relative importance of different reservoir species in nature. Using the conceptual framework of “reservoir potential,” which considers elements of both reservoir competence and vector-host contact, we review the wildlife reservoirs of Trypanosoma cruzi in the southern United States, where many species of triatomine vectors occur and wildlife maintain enzootic cycles that create a risk of spillover to humans, domestic dogs, and captive nonhuman primates that may develop Chagas disease. We reviewed 77 published reports of T. cruzi infection in at least 26 wildlife species across 15 southern states. Among the most well-studied and highly infected reservoirs are raccoon (Procyon lotor), woodrat (Neotoma spp.), and opossum (Didelphis virginiana), with aggregate overall infection prevalences of 36.4, 34.7, and 22.9%, respectively. Just over 60% of studies utilized methods from which an infectiousness index could be generated and show that raccoons and striped skunk (Mephitis mephitis) are among the most infectious wildlife hosts. Triatomine-host contact has sparsely been quantified in the southern United States, but 18 of the 24 host species previously identified to have been fed upon by triatomines are wildlife. Future studies to parameterize the reservoir potential model, especially to quantify wildlife infectiousness, vector-host contact, and the epidemiological importance of parasite strains maintained by wildlife, could open new doors for managing enzootic cycles and reducing T. cruzi spillover risk.